1 Archaeology of the Human Experience: An Introduction. Issue 1 (16th May 2016) - Hegmon, Michelle
ABSTRACT: The Archaeology of the Human Experience (AHE) is concerned with understanding what it was like to live in the past, an endeavor that speaks to established archaeological traditions and to much broader audiences. AHE has four components: (1) Investigating the conditions of life; (2) Understanding how those conditions came to be; (3) Considering how those conditions are part of, and affect, the larger social and cultural context; and (4) Exploring the experience of those conditions. Many established methods can be used to investigate the first three; the fourth raises delicate questions about whether and how we can know others. Future work will continue to develop systematic measures that might shed light on how and why conditions worsen or improve in some cases.